Molecular techniques for the assessment of Cr (VI) reduction by Bacillus thuringiensis - Deisy L. Guerrero Ceballos; Eduardo Ibargüen Mondragón; Pablo Fernández Izquierdo; Jhonatan Pinta Melo; Edith Mariela Burbano Rosero (Universitas Scientiarum)
Effluent pollution with Cr (VI) is a worldwide environmental problem. In the Pasto River (southeastern, Colombia), previous studies reported contamination with this metal at points near tanneries. To establish the role of Bacillus thuringiensis in Cr (VI) reduction in water from Pasto River, experiments were carried out with untreated Pasto River water (treatment 1), sterile Pasto River water inoculated with B. thuringiensis (treatment 2), and unsterilized Pasto River water inoculated with B. thuringiensis (treatment 3). All experiments were conducted in bioreactors with a controlled temperature of 20 °C and constant agitation for 156 h. Samples of 20 mL were taken every 12 h from each treatment to track Cr (VI) reduction levels and to confirm microorganism identity via molecular methods involving denaturing gradient gel electrophoresis (DGGE), restriction enzyme digestion profiles (RFLP), and bioinformatic analysis. Cr (VI) reduction was higher in treatment 3 (99:42 %) as opposed to treatment 2 (76:12 %) and treatment 1 (74:46 %). The molecular identity of B. thuringiensis was determined via sequencing of the 16SrRNA gene, and RFLP assessments in all three treatments revealed B. thuringiensis profiles. Since B. thuringiensis was present in all three treatments trough time, Cr (VI) reduction can be attributed to this bacterium.